Teaching Indonesian Language for Foreign Speakers in the State University of Surabaya: Strategies and Challenges - Heny Subandiyah; Haris Supratno; Resdianto Permata; Abdul Rosyid; Etik Minarti; Fithriyah Inda Nur Abida (Randwick International of Education and Linguistics Science Journal, 2023)
This paper aims to discuss the challenges and strategies of teaching Indonesian language to foreign speakers in State University of Surabaya. This study emphasizes on the strategies that can be used to improve the effectiveness of Indonesian language teaching for foreign speakers, given the various challenges that arise during the teaching-learning process. The study was conducted using qualitative method and in-depth interviews as the data collection tool. The respondents in this study were 10 Indonesian language teachers for foreign speakers from various countries in Asia and Europe. The research results show that the first problem is related to the complex grammar of the Indonesian language, which is difficult for foreign speakers to grasp, and the need to adapt teaching methods to suit the learning style and needs of foreign students. The strategies to overcome these problems include simplifying the teaching of grammar through the use of practical examples, employing active learning through games and role-playing, and having student-centered teaching methods that are tailored to the needs and preferences of foreign students.